(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One thing is common to do lay-off, retrenchment and closure of industrial establishment that is termination of service of workmen for short period or permanently. The employer has the genuine problem to do so, not with the feeling of retaliation. The provisions of this Act, prevent to him to do arbitrary lay-off, retrenchment and closure. Section 25M lays down the prohibition of lay-off, Section 25N conditions precedent to retrenchment of workmen and Section 25-O procedure for closure. Having under the conditions of provisions of Act, does the act of lay-off, retrenchment and closure.